The Development of the College Students' Experience of Family Harmony Questionnaire (CSEFHQ) - Zhan, Qisheng; Wang, Qin (Frontiers in Psychology, 2021)
The experience of family harmony, as an individual's subjective evaluation of harmonious family relations, has an important influence on the development of their physical and mental health. This study aimed to develop the College Students' Experience of Family Harmony Questionnaire that is fit for college students in China. On the basis of literature analysis and survey with questionnaires, five pairs of opposite assessment indexes were constructed in this paper, namely, Atmosphere of family (getting along vs. conflict), Responsibility to housework (undertaking housework vs. refusing housework), Time-sharing (sharing vs. self-isolatedness), Seeking help (help-seeking vs. avoidance), and Supporting family members (support-providing vs. indifference). Items of this questionnaire were collected from investigation, relevant scales, and discussion with experts. Here, 562 college students were selected for the pre-test and 696 for the formal test. The results showed that, except for the dimension of refusing housework, which has been deleted, other dimensions remain unchanged, and the final nine dimensions accounted for 66.03% of variance variation. Furthermore, the result of confirmatory factor analysis indicates that the model fit well with the data in construct validity [χ2/df = 2.71, Incremental Fit Index (IFI) = 0.90, Tucker–Lewis Index (TLI) = 0.89, Comparative Fit Index (CFI) = 0.90, root mean square error of approximation (RMSEA) = 0.05, standardized root mean square residual (SRMR) = 0.05]. The Cronbach's alpha (α) coefficient of this questionnaire was 0.97. The split-half reliability was 0.92, and the test–retest reliability was 0.75 for the total questionnaire. The total score of the questionnaire was significantly positively correlated with the total score of family function, family cohesion, family adaptability, and well-being (r = 0.73, 0.71, 0.75, 0.51, respectively, all p < 0.01), and it had a significant negative correlation with loneliness (r = −0.56, p < 0.01). The results showed that the final structure was reasonable, and reliability and validity conformed to the requirements of psychometrics. Therefore, the questionnaire developed in this study can be used as a valid instrument for assessing the experience of family harmony among college students in China.